A texture-driven model for male baldness - Balreira, Dennis Giovani; Figueiredo, Luiz Henrique De; Volkweis, Márcio; Walter, Marcelo (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI), 2022)
Male androgenetic alopecia, popularly known as male baldness, is a type of hair loss affecting more than half of males at some point in their lives. Despite several advances in medicine, the biological representation of baldness in computer graphics has not yet been an object of research. Designers still need to create models or use pre-existing ones without relying on any biologically plausible methodology available in the literature. This paper presents the first computational model of male baldness by simulating hair loss based on the Hamilton-Norwood classification. Given a 3D head model and its corresponding texture, our method models the hair dynamics with time by changing the texture according to a level of baldness using heat diffusion. Visual results are presented, together with an assessment from a dermatologist specializing in hair transplant, who considered the results very plausible and valuable for clinical usage. Beyond computer graphics applications, our method may also help in medical research, clinical use, and entertainment.